Cover Picture: Absolute Configuration from Different Multifragmentation Pathways in Light‐Induced Coulomb Explosion Imaging (ChemPhysChem 16/2016). Issue 16 (9th August 2016) - Pitzer, Martin; Kastirke, Gregor; Kunitski, Maksim; Jahnke, Till; Bauer, Tobias; Goihl, Christoph; Trinter, Florian; Schober, Carl; Henrichs, Kevin; Becht, Jasper; Zeller, Stefan; Gassert, Helena; et al.
Abstract : The Front Cover picture illustrates that light‐induced Coulomb explosions can image the absolute configuration of small molecules in the gas phase. Even partial fragmentation displays the signature of handedness. More information can be found in the Full Paper by M. Pitzer et al. onpage 2465 in Issue 16, 2016 (DOI:10.1002/cphc.201501118 ).